From illustrated text to picturebook: Astrid Lindgren’s “Mirabelle” - Agnes-Margrethe Bjorvand (Barnboken: Tidskrift för Barnlitteraturforskning, 2011)
During the last few years, several of Astrid Lindgren’s early stories have been turned into picturebooks. In this article I would like to take a closer look at what happens to a story when it develops from an illustrated text to a picturebook with an iconotext.